Injury acknowledgement by reduction of sports load in world-leading athletics (track and field) athletes varies with their musculoskeletal health literacy and the socioeconomic environment - Timpka, T.; Bargoria, V.; Andersson, C.; Jacobsson, J.; Gauffin, H.; Hansson, P.-O.; Adami, P. E.; Bermon, S.; Dahlström, Ö. (British Journal of Sports Medicine, 2023)
Objective: Although injury burden prompts elite athletics (track and field) athletes to engage in injury management, little is known about their health literacy. We investigated musculoskeletal (MS) health literacy in world-leading athletics athletes and associations with prechampionship injury acknowledgement by reduction of training load in different socioeconomic environments.